Family SES and maternal sensitivity predict infant patterns of regulatory behavior in Brazilian dyads. (December 2020) - da Costa Ribeiro, Camila; Teodoro, Ana Teresa Hernandes; dos Santos, Pedro Lopes; Lamônica, Dionísia Aparecida Cusin; Fuertes, Marina
Abstract: Infant's patterns of regulatory behavior contribute to infant socioemotional development and attachment. These behavioral patterns affect and are affected by the quality of mother-infant interaction. In most studies with full-term infants, the Social-Positive Oriented pattern (i.e., the infant's ability to soothe his/her emotions in the context of reciprocal and positive interactions) is the most prevalent pattern, followed by the Distressed-Inconsolable and by the Self-Comfort Oriented patterns. However, these patterns are understudied in other populations beyond the US and European countries. The current research addresses this gap by studying the regulatory behavior patterns and their association with mother-infant interactions in Brazilian dyads and evaluating the association of these regulatory patterns with demographics. Analyses were based on data collected for 40 infants (20 boys, 20 girls) and their mothers. Infants' regulatory behavior patterns were evaluated in the Face-to-Face Still-Face paradigm and mother-infant interaction was evaluated during free play at 3 months age. Notably, our findings indicate that Distressed-Inconsolable was the most prevalent pattern in this sample; followed by the Social-Positive Oriented and the Self-Comfort Oriented patterns. Furthermore, we found that maternal sensitivity and family SES (social-economic status) predicted infant patterns of regulatory behavior. Highlights: Distressed-Inconsolable regulatory behavior pattern is the most prevalent among Brazilian infants Maternal sensitivity and infant cooperation are associated with Social-Positive pattern of regulatory behavior Maternal sensitivity and family SES predicted infant patterns of regulatory behavior